PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA DI DESA TAMANSARI KECAMATAN LICIN KABUPATEN BANYUWANGI - Sulistyowati, Desy; Rahayu, Sri; Permatasari, Safrieta Jatu (JURNAL KATARSIS, 2024)
Comunity Participation In The Development Of Tourism Village In Tamansari Village, Licin District, banyuwangi Regency. Basically, the participation of the community in all tourism village development activities is nothing but the aim of obtaining and enjoying the results of each stage that has been passed. The form of community participation in efforts to develop Tamansari Tourism Village is to take advantage of natural resources, namely its natural beauty by making the potential of the area a tourist attraction, so that various participations are carried out by the community. In the development of the Tamansari Tourism Village, community participation can be seen in various forms, including physical participation and non-physical participation. Considering the natural beauty that exists in Tamansari Village is a strong attraction for tourists, then in its development it is very necessary to have the participation of the community involving all walks of life.